Mathematical modeling of sputtering-induced surface roughness - Ali, Mohammad Yeakub; Hung, N. P.; Yuan, S. (2001)
This paper develops a sputtering-induced surface roughness model. The model is necessary to control surface roughness of a replicating tool that is machined by focused ion beam (FIB). The significant Gaussian intensity level of FIB profile is determined first, the mathematical model of surface roughness is then developed. The surface roughness function is the combination of the beam function and the material function. The beam function includes ion type, acceleration energy, ion flux, ion beam intensity distribution, tailing and neighboring of the successive beams, and dwell time. The cumulative intensity at a location is calculated by the algebraic summation of individual beam intensity delivered to every pixel successively. The material function includes the inherent material properties related to the ion beam micromachining, such as crystallographic structure and orientation, atomic density, binding energy. Experimental data for silicon verifies the validity of this model.